How and when does personal life orientation predict well‐being?. Issue 4 (30th September 2022) - Gillet, Nicolas; Morin, Alexandre J. S.; Huyghebaert‐Zouaghi, Tiphaine; Austin, Stéphanie; Fernet, Claude
Abstract: We examined the direct and indirect––as mediated by job satisfaction––effects of personal life orientation on life satisfaction. We also examined whether these direct and indirect associations differed between employees working onsite or remotely. Using data from 432 employees (152 working onsite and 280 working remotely), our results revealed that personal life orientation was positively related to life satisfaction and negatively related to job satisfaction. Moreover, both of these direct associations were stronger among onsite employees than among remote employees. As a result, the indirect effects of personal life orientation on life satisfaction were significantly mediated by job satisfaction among employees working onsite, but not among employees working remotely. This study thus reveals that working remotely may act as a double‐edged sword by buffering the negative effects of personal life orientation on job satisfaction, but also by limiting the positive effects of personal life orientation on life satisfaction.